2012
DOI: 10.1007/s10936-012-9205-7
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Role of Gesture in Linguistic Development: A Developmental Trajectory and a Cross-Cultural Comparison Between British and Finnish Children

Abstract: We studied how gesture use changes with culture, age and increased spoken language competence. A picture-naming task was presented to British (N = 80) and Finnish (N = 41) typically developing children aged 2-5 years. British children were found to gesture more than Finnish children and, in both cultures, gesture production decreased after the age of two. Two-year-olds used more deictic than iconic gestures than older children, and gestured more before the onset of speech, rather than simultaneously or after s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 37 publications
3
20
1
Order By: Relevance
“…Overall, children produced more pointing and representational gestures in combination with speech than gestures alone. This is consistent with previous findings that 2‐ and 3‐year‐old children use bimodal combinations more frequently than unimodal gesture expressions in naming tasks (e.g., see Marentette et al., , and Stefanini et al., , for Italian children; Hall et al., , for Australian children; Huttunen et al., , for British children; and Marentette et al., , for Canadian English‐speaking children). However, the Italian children produced significantly more crossmodal combinations of speech and representational gestures than the two English‐speaking groups, who did not differ in this respect.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Overall, children produced more pointing and representational gestures in combination with speech than gestures alone. This is consistent with previous findings that 2‐ and 3‐year‐old children use bimodal combinations more frequently than unimodal gesture expressions in naming tasks (e.g., see Marentette et al., , and Stefanini et al., , for Italian children; Hall et al., , for Australian children; Huttunen et al., , for British children; and Marentette et al., , for Canadian English‐speaking children). However, the Italian children produced significantly more crossmodal combinations of speech and representational gestures than the two English‐speaking groups, who did not differ in this respect.…”
Section: Discussionsupporting
confidence: 91%
“…Next, we looked at whether the frequencies of pointing and representational gestures produced alone or with the accompanying spoken responses (i.e., unimodal vs. bimodal gesture productions) are equally represented across countries. Typically, 2‐ and 3‐year‐old children use gesture plus speech combinations (i.e., combinations of words with pointing or representational gestures) more frequently than unimodal gesture expressions in naming tasks, which has been shown for Italian children (Marentette et al., , Stefanini et al., ), Australian children (Hall, Rumney, Holler, & Kidd, ), British children (Huttunen et al., ), and Canadian English‐speaking children (Marentette et al., ).…”
Section: The Current Studymentioning
confidence: 93%
See 1 more Smart Citation
“…() reported no group difference in representational gesture frequency. In contrast, Huttunen, Pine, Thurnham, and Khan () found that Finnish preschool‐aged children produced fewer gestures, both deictic and representational, than British children. This effect was particularly noteworthy among the 2‐year‐olds: None of the Finnish children produced representational gestures, while the British children averaged two representational gestures per child in the task.…”
Section: Representation In Elicited Pantomimementioning
confidence: 92%
“…In a study by Huttunen et al (2013), British and Finnish children aged 2 to 5 years had to accomplish a picture-naming task. Both groups used more pointing than iconic gestures at the age of 2.…”
Section: Interaction Between Language Development and Gesturesmentioning
confidence: 99%